Pathogenetic Justification of a New View on the Treatment of Angle-Closure Glaucoma - N. A. Bakunina; L. N. Kolesnikova; J. M. Salmasi; L. M. Balashova (Oftalʹmologiâ, 2021)
Purpose. To study the effectiveness of vascular, anti-inflammatory and fibrinolytic therapy, to conduct a comparative assessment with treatment without vascular therapy in patients with angle-closure (ACG) and mixed glaucoma.Methods. A total of 55 patients with angle-closure and mixed glaucoma, mainly with hypermetropic refraction of varying degrees, were examined: 7 people with acute glaucoma attack, 6 people with subacute glaucoma attack (group 1, with anti-inflammatory treatment), 7 people with acute glaucoma attack and 6 people with subacute glaucoma attack (group 2, with vascular treatment), 14 people with chronic angle-closure glaucoma (group 3) and 15 people with mixed glaucoma (group 4). All patients underwent an ophthalmological examination, which included visometry, refractometry, tonometry, computer perimetry, OCT and OCT angiography, and an ELISA analysis to determine cytokines.Results. The administration of the drug Pentoxifylline as a cytokine blocker and antiplatelet agent in ACG contributed, in our opinion, to an improvement in visual acuity, perimetry (MD), an increase in the density of capillaries of the deep vascular plexus at the level of lamina cribrosa in the peripapillary zone (%), i.e. improved blood circulation in the vessels of the optic nerve disc and also contributed to the blockade of cytokines, mainly in the 2-nd group of patients. In our opinion, a personalized approach to the treatment of ACG is to maintain the improvement of blood circulation in the peripapillary zone by prescribing a course of treatment with Pentoxifylline for 6 months after surgery. After phacoemulsification, there was a significant increase in the density of capillaries of the deep peripapillary vascular plexus at the level of lamina cribrosa (p ≤ 0.05) (51.0 ± 3.5 %), and after further treatment with Pentoxifylline, the capillary density continued to increase in 2–4 groups in the next 6 months of follow-up. The thickness of RNFL (Retinal nerve fiber layer, structural parameter) decreased due to a decrease in edema in 1–2 groups, slightly increased in 3–4 groups, in our opinion, due to improved blood circulation. Increased reperfusion in the capillaries of the deep plexus during normalization of IOP in glaucoma patients and further treatment with pentoxifylline indicates the effectiveness of the proposed treatment in addition to surgical treatment. The results obtained emphasize the advantages of the proposed therapy for the treatment of patients with angle-closure and mixed glaucoma.Conclusion. To date, there are no clear recommendations of vascular therapy for the treatment of patients with ACG and mixed glaucoma, which creates the need for its addition to treatment regimens, taking into account the vascular component of ACG and mixed glaucoma.